2014
DOI: 10.1080/01425692.2014.939265
|View full text |Cite
|
Sign up to set email alerts
|

Learning, literacy and identity: ‘I don’t think I’m a failure any more’

Abstract: The impact of participation in adult literacy programmes on learners' identities is examined through an interrogation of their past and current experiences and the assessment of the effect of particular pedagogies. The findings show how learners' positive experiences in their programmes had caused them to re-evaluate their previous understandings and enabled the construction of new identities as people that are able to learn. These changes had come about through the challenging of negative discourses, the crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The curriculum they have offered has instead been based on a 'funds of knowledge' approach (González, Moll and Amanti, 2005), which other research has suggested (e.g. Tett, 2016), can help learners to develop the effective strategies and skills they already use rather than being seen as having individual deficits that need to be corrected. As we have shown, the values that drove the practitioners' pedagogical practices was a focus on the learners' goals and so the learning arose out of 'the inherently socially negotiated character of meaning … in, with, and arising from the socially and culturally structured world' (Lave and Wenger 1991, 51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curriculum they have offered has instead been based on a 'funds of knowledge' approach (González, Moll and Amanti, 2005), which other research has suggested (e.g. Tett, 2016), can help learners to develop the effective strategies and skills they already use rather than being seen as having individual deficits that need to be corrected. As we have shown, the values that drove the practitioners' pedagogical practices was a focus on the learners' goals and so the learning arose out of 'the inherently socially negotiated character of meaning … in, with, and arising from the socially and culturally structured world' (Lave and Wenger 1991, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Third, changes in the welfare benefits meant that claimants needed increased literacy skills to apply for JSA because applications had to be made on-line so people that had had sufficient literacy to manage their daily lives were no longer able to cope. Finally those that did find a place on a programme were often given a curriculum that prioritised narrow employment-skills focused outcomes that neither respected learners' own goals nor valued their life experiences and this can have a negative impact on their learning (Tett, 2016).…”
Section: Human Capital Discourses In Transnational and National Educamentioning
confidence: 99%
“…Individual teachers can be very influential in a student's learning career and research has shown that students can change their learning disposition as a result of a positive student/tutor relationship (Tet, 2016). The idea that students can change how they see themselves as learners speaks to a core motivation for learning developers.…”
Section: Writing and Identitymentioning
confidence: 99%
“…This narrowing of literacy toward a purely functional model is, however, heavily contested. Indeed, in addition to the seminal contribution of Street (1984) on the autonomous and ideological models of literacy, recent theorizations have focused upon the social nature of literacy (Duckworth, 2014;Tett, 2016).…”
Section: Theoretical Approaches A) Social Approaches To Literacymentioning
confidence: 99%